The Influence of Service Quality on Repeat Purchases at the Hajj and Umrah Travel Services Bureau at PT Ambassador Tour and Travel - Fajar Firmansyah; Kiagus Muhammad Amran; Nur Aziz Sugiharto (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2025)
The number of Umrah pilgrims in Indonesia has increased significantly in recent years, in line with the Saudi Arabian government's reopening of Umrah pilgrims from outside Arabia after a two-year ban in 2020 and 2021 due to COVID-19. This increase is influenced by factors such as stable economic growth, improvements in facilities and services, and innovations in access and communication technology that make it easier to plan Umrah trips online. The Indonesian government's support for implementing the Umrah pilgrimage is also essential. This has led to a significant increase in the number of Umrah pilgrims in Indonesia, as reported in the 1445 H December 2023 season. PT Ambassador Tour and Travel also recorded increased Umrah pilgrims, standing out with its commitment to service quality. The service quality factor is the primary consideration for prospective pilgrims when choosing a travel agent, and maintaining customer satisfaction and ensuring repeat purchases are the keys to business success in a competitive industry. Further research is planned to explore the influence of service quality on repeat purchases at PT Ambassador Tour and Travel. This research applies a quantitative survey approach with an associative approach, which involves surveying PT Ambassador tours and travel Umrah pilgrims. In its implementation, this survey method presents a structured questionnaire to respondents. The sampling technique in this research used a non-probability sampling technique with a purposive sampling technique with a total of 145 respondents. The data analysis technique used is Statistical Program for Social Science (SPSS) version 23. With the expected results, service quality and repeat purchases will have a positive and significant influence; apart from that, this research can contribute to further study